Diagnostic accuracy of neutrophil-to-lymphocyte ratio in type 2 diabetic nephropathy: a meta-analysis - Wang, Yan; Liu, Xiaohua; Xiao, Zhenwen (Frontiers in Endocrinology, 2025)
BackgroundDiabetic nephropathy (DN) represents one of the most prevalent microvascular complications of type 2 diabetes mellitus (T2DM). The pathogenesis of DN is significantly influenced by the inflammatory response. Thus, the current meta-analysis aimed to assess the diagnostic accuracy of neutrophil-to-lymphocyte ratio (NLR) in early DN and DN.MethodsCochrane, Pubmed, Embase, and Web of Science were retrieved from database establishment to August 31, 2024. The Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) was utilized to assess the quality of included studies. This meta-analysis was carried out via Stata16.0 and Revman 5.3 software.ResultsFinally, this meta-analysis incorporated 18 studies, of which 5 were early DN studies, involving 232 patients with early DN, and 13 were DN studies, involving 4,818 patients with DN. The results indicated that the diagnostic sensitivity of NLR for early DN was 0.83 [95% CI: 0.60-0.94], the specificity was 0.76 [95% CI: 0.61-0.86], and the area under the receiver operating characteristic curve (AUROC) was 0.85 [95% CI: 0.81-0.88]. The diagnostic sensitivity of NLR for DN was 0.73 [95% CI: 0.67-0.79], the specificity was 0.70 [95% CI: 0.59-0.79], and the AUROC was 0.78 [95% CI: 0.74-0.81].ConclusionsNLR exhibited moderate performance in diagnosing both early DN and DN, and its diagnostic accuracy was higher in early DN than in DN. Due to the limitations of existing studies, further studies are required to verify the findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024591926.